Reconstruction of Legal Protection for Aesthetic Clinic Patients - Siska Diana Sari (Alliance of Health Activists (AloHA), 2021)
The protection of aesthetic beauty clinic patients is important because of the increasing number and development of beauty clinic businesses, and the emergence of many problems and cases related to its implementation, as a result of implementing actions that are not in accordance with the relevant laws and regulations. This raises the need for protection against health risks arising from losses for services in beauty clinics that are not in accordance with statutory regulations in the field of health law and consumer protection law. The state is obliged to provide protection related to the implementation of constitutional rights to legal protection and the right to health, so that beauty clinic business actors obey all applicable regulations related to its implementation, increasing the responsibility as a business actor towards its consumers. In reality, the phenomenon of this beauty clinic case is like an iceberg, large but not visible on the surface, because the majority of patients from the middle to upper economic class feel ashamed and do not want to bother reporting it, ideally organizing aesthetic beauty clinics is based on applicable laws and regulations. The state must be able to provide legal certainty and protection to aesthetic beauty clinic patients with good regulatory and institutional and risk litigation. Keywords: aesthetics; protection; law; patients; clinics